Deagrarianization and Local Food Security Strategy for Peasant Communities in Rural Central Java - Pujiriyani, Dwi Wulan; Soetarto, Endriatmo; Santosa, Dwi Andreas; Agusta, Ivanovich (Universitas Negeri Semarang, 2019)
Food security is one of the important issues in the study of deagrarianization. In macro level, deagrarianization can weaken food security which is indicated by the ability of food production which continues to decline due to the structural transformation of the economy from agriculture to non-agriculture. The purpose of this study is to determine food security at the community level when the symptoms of macro deagrarianization have occurred. This research is conducted by qualitative methods. An ethnosociological approach is used by combining community case study methods and ethnographic methods. The results show that food security at the community level is still well-maintained. Deagrarianization has not diminished the ability of the community to meet their food needs. Communities have internal mechanisms that secure their food sufficiency through food strategies and non-food strategies. The food strategy is carried out through saving yields for grain stores (family food barns) and reduce the amount of consumption. Meanwhile the non-food strategy is carried out through diversification of livelihoods by relying on available extractive landscapes. Swamps (balongan) are used as a food source that provides various types of local fish, crabs and snails as a source of protein for family consumption and also for sale to local collectors.